4D printing of ZnO nano-filler shape memory polymer - Yan, Yankun (Nanyang Technological University, 2021)
The application of nanoparticles in vat photopolymerization technologies has found great potential in enhancing the properties of the material in terms of structural, functional and printing. However, some nanoparticles superimpose curing issues during the printing process which limits the fabrication methods. Zinc Oxide (ZnO), in nanoparticle form, are often utilized as additive in medical fields as well as an UV absorber in applications related to light. But due to its light absorbing and blocking effects, ZnO is seldom deployed in light processing 3D printing technologies. This Final Year Project presented the feasibility study of 3D printing of ZnO nanoparticles as additive using Digital Light Processing (DLP) and its effects in curing, print precision, mechanical and thermal properties. The ZnO nanoparticle was dispersed into the self-formulated resin via mechanical mixing and ultrasonication. The printing parameters were determined through cure depth tests in addition with try and error for the parameters related to adhesion properties. Standard tensile tests were carried out to investigate the mechanical properties, Dynamic Mechanical Analysis (DMA) and Differential scanning calorimetry (DSC) tests were performed to evaluate the thermal properties including glass transition temperature and degree of polymerization. The effect of post curing was also investigated by comparing the mechanical and thermal properties of cure and uncured samples. Shape Memory Effects (SME) including shape recovery rate and shape recovery percentage were investigated and quantified through simple self-designed tests. Print quality and print accuracy tests were performed to compare the performance of the novel developed base formulation and with the addition of ZnO nanoparticles. Through the tests conducted, conclusions were obtained that resins with ZnO nanoparticles as additive can successfully be printed using DLP technology and the optimal printing parameters were determined. An increase of 7% in strength and 16% in modulus were observed for the ZnO formulation while with no significant variation in glass transition temperature of 52.77℃. SME tests yielded a shape recovery percentage of more than 99% after 3 deformation-recovery cycle and this has approved the excellence SME properties of this ZnO formulation. In addition, with the participation of ZnO nanoparticles, distinct print precision was achieved as compared to the novel base formulation. Obvious improvements in printability and print quality were observed for the addition of ZnO into the hard-to-cure resins.